2006
DOI: 10.1016/j.juro.2006.06.066
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Dihydrotestosterone Level in the Prostate and Prostate Cancer Aggressiveness Using the Gleason Score

Abstract: Patients with Gleason score 7 to 10 prostate cancer have low dihydrotestosterone in the prostate, although there were no significant differences between patients with Gleason score 7 to 10 vs 6 or less prostate cancer with respect to serum androgens. Low dihydrotestosterone in cases of aggressive prostate cancer is probably sufficient to activate androgen receptor expression and propagate tumor growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 19 publications
1
40
1
Order By: Relevance
“…However, the present study demonstrated that: (1) these measurements could be conducted using the small amounts of tissue obtained by needle biopsy, rather than excised prostate tissues; and (2) androgen measurements could be carried out much more precisely than by RIA, by using LC-MS/MS. Nishiyama and colleagues used LC-MS/MS and reported that 47 patients with prostate cancer with Gleason scores of 7-10 had low DHT levels in the prostate, as shown by univariate analysis [9]. In the current study, we found that low tissue DHT levels were associated with a high % positive cores.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…However, the present study demonstrated that: (1) these measurements could be conducted using the small amounts of tissue obtained by needle biopsy, rather than excised prostate tissues; and (2) androgen measurements could be carried out much more precisely than by RIA, by using LC-MS/MS. Nishiyama and colleagues used LC-MS/MS and reported that 47 patients with prostate cancer with Gleason scores of 7-10 had low DHT levels in the prostate, as shown by univariate analysis [9]. In the current study, we found that low tissue DHT levels were associated with a high % positive cores.…”
Section: Discussionsupporting
confidence: 68%
“…Several studies of androgen concentrations in prostate tissues have used bulk tissues such as prostatectomy specimens, and androgen levels have been measured by RIA methods [3,4,9,[12][13][14]. However, the present study demonstrated that: (1) these measurements could be conducted using the small amounts of tissue obtained by needle biopsy, rather than excised prostate tissues; and (2) androgen measurements could be carried out much more precisely than by RIA, by using LC-MS/MS.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…We revealed that the DHT levels in the prostate in patients with Gleason scores of 7 to 10 were significantly lower than those with Gleason scores of 6 and under, although there were no significant differences between the patients with Gleason scores of 7 to 10 and the patients with Gleason scores of 6 and under prostate cancer with respect to serum levels of androgens. [27] The result of the association between the DHT level in the prostate and the Gleason score gives useful information to predict the biological aggressiveness of prostate cancer and consider the treatment of the patients with such cancers. One hypothesis as to the correlation between clinical aggressiveness and low androgen levels in the prostate is that the hormonal milieu with low androgen levels might be varied enough to disrupt the normal growth and maintenance of the prostate tissue, and may cause the resultant compensatory hyperplasia that increases the risk of a consequent selection of androgen independent, aggressive prostate cancer formation due to low androgen levels.…”
Section: Prostate Cancer Aggressiveness and The Androgen Milieu In Thmentioning
confidence: 99%
“…Morgentaler 18 demonstrated the association between low serum testosterone with higher Gleason grade cancer. In addition, Nishiyami et al 19 reported that intraprostatic dihydrotestosterone levels were significantly reduced in men with Gleason X7 cancer compared with men with Gleason score p6. Based on these studies, we decided to also examine the relationship of serum testosterone with PSAd in our cohort of patients on active surveillance.…”
mentioning
confidence: 99%